Agromorphological characterization of Phaseolus spp., accessions in Amazonas region, Peru (Bioagro, 2024)
Peru has a high genetic diversity of Andean legumes, especially of the genus Phaseolus. Its identification through agromorphological descriptors is essential to promote its conservation, which allows the development of genetic improvement studies. Under this scenario, the objective of the present work was to characterize morphologically and agronomically 58 accessions of common bean (Phaseolus spp) deposited in the germplasm bank of the Instituto Nacional de Innovación Agraria del Perú. For this purpose, 24 quantitative and 18 qualitative descriptors were used to evaluate the phenology of each accession. Cluster analysis and multiple correspondence analysis identified the formation of four groups according to their similar characteristics. The largest number of accessions were located in the third and fourth groups. However, the seven accessions that made up the second group exhibited promising characteristics for their high productivity (2777.86 kg/Ha), with white seeds, of acceptable dimensions, with early epigeal germination (10 days), ovate-lanceolate leaves of indeterminate growth (174.79 cm plant height) that develop numerous guides. Besides having a prolonged flowering (33.86 days) with pink and white petals, which give rise to a greater number of green pods (66.71 per plant) until they reach physiological maturity. These qualities make them a valuable source for the appropriate implementation of future breeding programs.
Keywords: Andean legumes; conservation; descriptors; diversity; germplasm bank